2015
DOI: 10.1002/jcb.25151
|View full text |Cite
|
Sign up to set email alerts
|

Double Stranded RNA‐Dependent Protein Kinase is Necessary for TNF‐α‐Induced Osteoclast Formation In Vitro and In Vivo

Abstract: Double-stranded RNA-dependent protein kinase (PKR) is involved in cell cycle progression, cell proliferation, cell differentiation, tumorgenesis, and apoptosis. We previously reported that PKR is required for differentiation and calcification in osteoblasts. TNF-α plays a key role in osteoclast differentiation. However, it is unknown about the roles of PKR in the TNF-α-induced osteoclast differentiation. The expression of PKR in osteoclast precursor RAW264.7 cells increased during TNF-α-induced osteoclastogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
(51 reference statements)
1
23
0
Order By: Relevance
“…The generation of OCs from RAW264.7 cells 16 or mouse bone marrow cells 17 was performed as previously described. The cells were cultured in Eagle's minimal essential medium a modification (SigmaAldrich) supplemented with 10% FBS, L-glutamine, and 50 mg/mL penicillin/streptomycin.…”
Section: Oc Formationmentioning
confidence: 99%
“…The generation of OCs from RAW264.7 cells 16 or mouse bone marrow cells 17 was performed as previously described. The cells were cultured in Eagle's minimal essential medium a modification (SigmaAldrich) supplemented with 10% FBS, L-glutamine, and 50 mg/mL penicillin/streptomycin.…”
Section: Oc Formationmentioning
confidence: 99%
“…However, most of the previous studies revealed the roles of PKR in confronting the chronic cellular stresses, including regulating metabolic homeostasis23, mediating TNF-α induced osteoclast formation26 and systolic overload-induced congestive heart failure21, et al . In this study, we investigated in the face of H 2 O 2 treatment on NCM, an acute and drastic cellular stress, whether PKR is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p38 MAPK signalling pathways is also implicated in mediating RANKL-induced osteoclastogenesis, suggested the increased TNF-α mRNA abundance induced by RANKL is mediated by activating this signalling cascade leading to TNF-α transcriptional stabilities. Besides that, most recently, Shinohara et al 141 have reported that double-stranded RNA-dependent protein kinase (PKR) association is necessary for TNF-a induced RAW-OCs formation by p38MAPK, and ERK signalling ( Figure 2).…”
Section: Tnf-α and Its Role In R Aw-o C S Induc Tionmentioning
confidence: 98%
“…Specifically, Zou et al 136 explained this autocrine manner as RANKL induction of osteoclastogenesis is accompanied by a rapid and transient increase in TNF-α mRNA abundance in the precursor cell; specific anti-TNF-α antibodies or antibodies directed against TNF receptor type I inhibit the osteoclastogenic activity of RANKL in RAW264.7cells. Besides that, most recently, Shinohara et al141 have reported that double-stranded RNA-dependent protein kinase (PKR) In fact, AU-rich elements (AREs) of 3′ untranslated region (3′-UTR), as cis-element, involved in the regulation of TNF-α mRNA transcription 137,138.…”
mentioning
confidence: 99%